Preoperative Embolization of Venous Malformations Using n-Butyl Cyanoacrylate. (May 2018) - Uller, Wibke; El-sobky, Sherif; Alomari, Ahmad I.; Fishman, Steven J.; Spencer, Samantha A.; Taghinia, Amir H.; Chaudry, Gulraiz
Purpose: The purpose of this study was to evaluate the safety and efficacy of preoperative percutaneous n -butyl cyanoacrylate (nBCA) embolization of venous malformations in children. Material and Methods: Clinical data were retrospectively reviewed in children who underwent embolization using nBCA followed by resection of venous malformations. Results: A total of 17 embolizations were performed in 14 patients (9 females, mean age: 5.5 years; median age: 3 years; range 0.1-16 years). The venous malformations involved the lower extremity and the knee joint (n = 7), the trunk (n = 4), head and neck (n = 2), and hand (n = 1). n -Butyl cyanoacrylate was diluted with iodized oil at a ratio of 1:3 to 1:5. The mean and median volume of nBCA per procedure were 2.1 and 2 mL, respectively (range: 0.5-8 mL). There were no complications associated with the procedures. The mean and median time between final embolization and resection were 3.6 and 2 days, respectively. All children underwent successful resection of the symptomatic lesions. The estimated mean and median blood loss were 75 and 50 mL, respectively (range: 5-350 mL). The postprocedure course was uneventful, the days to discharge ranged between 1 and 6 days (mean 3 days). Conclusion: Initial results suggest that preoperative percutaneous n -butyl cyanoacrylate embolization of venous malformations is safe and effective in children, with the potential for minimizing blood loss and inpatient stay.